A HEROÍNA E A PROSTITUTA: A ANALOGIA ENTRE AS PERSONAGENS MACABÉA E CARLOTA EM "A HORA DA ESTRELA", DE CLARICE LISPECTOR - Marques, Jessica Souza Pereira (Inventário, 2024)
The purpose of this article is to explain one of the literary aspects of the writer Clarice Lispector: the fictional character, with an emphasis on the construction of the identity profile of the female characters Macabéa and Madama Carlota. The aim is to draw up a psychological profile, based on theories about the construction of the fictional character. In addition, this study will also draw a parallel between the characters studied, with slight comparisons, as well as situating and describing how these female characters are portrayed in Lispector’s fiction. In this way, the characters mentioned in The Hour of the Star (1998) will be analyzed in a theoretical approach, based on the works Character in Fiction, by Antonio Candido (2014) and The Character by Beth Brait (1985), as well as other theorists, who will help to elaborate these literary profiles. In this sense, we sought to understand, together with the theoretical analysis of the fictional character, the portrait of Clarice’s female characters.